Peran Ekonomi Digital dalam Meningkatkan Inklusivitas Sosial dan Pemberdayaan Ekonomi Masyarakat - Sihotang, Mujuranto (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
This research aims to explore the role of the digital economy in enhancing social inclusiveness and community economic empowerment. Along with the rapid development of information technology, the digital economy provides opportunities for marginalised communities to access markets, information and financial services, and empowers micro, small and medium enterprises (MSMEs) to grow their businesses. However, the research also identified a significant digital divide between urban and rural areas, and low digital literacy that hinders access to the potential of the digital economy for many. More inclusive policies and digital literacy training are needed to ensure the digital economy can have an equitable impact. This research recommends the need to strengthen technological infrastructure and policies that support equitable digital adoption to promote economic empowerment and social inclusiveness